Depiction of Vamana, an avatar of Vishnu - Temples of India Project Team (Jio Institute, 2024)
On the kakshasana (seat backs), the depiction of Vamana, an avatar of Vishnu, stands prominently. Vamana is portrayed with four arms, although two are damaged. In his upper right hand, he holds a pustaka (book). This attribute holds significant symbolism, as Vishnu in his Vamana avatar assumes the form of a Brahmin, embodying the essence of divine wisdom contained within the Vedas.